Compressive behavior of concrete-filled aluminum alloy tube (CFAAT) stub column with inner carbon steel tube. (August 2021) - Ye, Yong; Wang, Lan; Zhang, Shi-Jiang; Zhang, Chen-Yang
Abstract: An additional inner carbon steel tube is employed in the concrete-filled aluminum alloy tube (CFAAT) to further enhance the load-carrying capacity of this composite member. The axial compressive behavior of CFAAT stub column with inner carbon steel tube is experimentally investigated in this paper. Six CFAAT specimens and four corresponding hollow metal tubes were tested under axial compression, and the test parameters included the dimensions of inner tube and the concrete strength. The experimental results showed that, the hollow metal tubes failed due to both inward and outward local buckling, while only outward local buckling was observed in the CFAAT specimens. The additional inner carbon steel tube contributed to the increase in both strength and ductility of the CFAAT columns. The ultimate strength tended to increase with increasing the inner-tube dimensions or the concrete strength, while a higher concrete strength led to a reduced ductility of the composite member. Finally, the contribution of inner carbon steel tube to the load-carrying capacity of CFAAT columns was analyzed.